Raising the bar in anticancer therapy:recent advances in, and perspectives on, telomerase inhibitors - Zisterer, Daniela; Saraswati, A Prasanth; Relitti, Nicola; Brindisi, Margherita; Gemma, Sandra; Butini, Stefania; Campiani, Giuseppe (My University, 2019)
Telomerase is a ribonucleic reverse transcriptase enzyme that uses an integral RNA component as a template to add tandem telomeric DNA repeats, TTAGGG, at the 3′ end of the chromosomes. 85–90% of human tumors and their derived cell lines predominantly express high levels of telomerase, therefore contributing to cancer cell development. However, in normal cells, telomerase activity is almost always absent except in germ cells and stem cells. This differential expression has been exploited to develop highly specific and potent cancer therapeutics. In this review, we outline recent advances in the development of telomerase inhibitors as anticancer agents.
PUBLISHED
Keywords: Telomeres; Telomerase inhibitors; Reverse transcriptase; Chromosomes; OSCC; Cancer; Cancer